Effect of video-based interventions on emergence delirium in pediatric patients: a systematic review and meta-analysis of randomized controlled trials - Yue Wang; Lifang Wang; Nan Liang; Kan Wang (Jornal de Pediatria)
Objective: Emergence delirium is frequently observed in pediatric patients. With advancements in video-based interventions, such as cartoons, video games, and virtual reality, these modalities may contribute to a reduced incidence of emergency delirium among children. However, robust evidence supporting their efficacy remains necessary. Methods: The authors conducted a systematic search across multiple databases, including Embase, MEDLINE, and Cochrane Library, to identify all randomized controlled trials comparing video-based interventions with control treatments in pediatric emergence delirium. Data were aggregated and analyzed using Review Manager 5.4 to evaluate the effectiveness of video-based interventions. Results: The analysis included eight randomized controlled trials comprising 872 children. The intervention group showed a trend toward lower Pediatric Anesthesia Emergence Delirium scores (p = 0.10) and fewer emergence delirium events (p = 0.52). Seven studies demonstrated that video-based interventions significantly reduced preoperative anxiety, as indicated by decreased scores on the modified Yale Pre-operative Anxiety Scale (p < 0.00001). Anesthesia duration did not significantly differ between the intervention and control groups (p = 0.16). Notably, subgroup analyses revealed a significant reduction in Pediatric Anesthesia Emergence Delirium scores among children under seven years of age (p = 0.001). Conclusions: Video-based interventions were linked to lower Pediatric Anesthesia Emergence Delirium scores and a decreased incidence of emergence delirium events. However, these results did not reach statistical significance across the broader sample. Notably, in children under seven, these interventions significantly reduced the scores. Level of evidence: III